Volume 8: Microturbines, Turbochargers, and Small Turbomachines; Steam Turbines 2018
DOI: 10.1115/gt2018-76498
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Flow Effects on Steam Turbine Last Stage Blades at Very Low Load Operating Condition

Abstract: Unsteady aerodynamic and structural interactive analysis method for design and development of highly efficient low pressure last stage blades and results of its main application on very low load conditions are reported in this paper. Main features of this method are the enhanced analysis scope including very low load conditions and validations using measured data of real steam turbines including very low load conditions as well. Our schemes for this project were introducing boundary conditions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Further research by Sigg and Rice 12 showed that the system RI was influenced by the exhaust shape. Nonsynchronous unsteady aerodynamic excitations in the last stage were also found by Liu et al 13 and Tanuma et al 14 Besides the flow fluctuation, Beevers et al 15 and Mambro et al 16,17 found that in this region, due to lack of axial flow, heat was difficult to dissipate through convection, and the temperature of the flow increased abnormally, which caused the LSMB tip and the casing to be in high temperature.…”
Section: Introductionmentioning
confidence: 57%
“…Further research by Sigg and Rice 12 showed that the system RI was influenced by the exhaust shape. Nonsynchronous unsteady aerodynamic excitations in the last stage were also found by Liu et al 13 and Tanuma et al 14 Besides the flow fluctuation, Beevers et al 15 and Mambro et al 16,17 found that in this region, due to lack of axial flow, heat was difficult to dissipate through convection, and the temperature of the flow increased abnormally, which caused the LSMB tip and the casing to be in high temperature.…”
Section: Introductionmentioning
confidence: 57%
“…In recent years, the occurrences of RI in steam turbines are frequently reported through tests or numerical simulations. 1820…”
Section: Introductionmentioning
confidence: 99%
“…Although it has not been clearly proposed in researches of steam turbines, the characteristics of blade dynamic stress measurements in Refs. 18 and 26 showed that with the continuous change of operating parameters, the blade dynamic stress would maintain a relatively high level within a certain range after an abnormal rise. It seems to indicate that the abnormal vibrations of LP steam turbine LSMBs under low-load conditions are not only resonance, but more likely to be lock-in phenomenon within a certain frequency range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow research in steam turbines at low regimes is performed mainly using numerical simulations of the flow [1,2]. In certain cases experimentally obtained results are available [3], when experiments were performed on model steam turbines. It is valuable to compare both methods, which ensures two-way data validation [4].…”
Section: Introductionmentioning
confidence: 99%